Pernikahan Endogami Keturunan Arab Perspektif Hukum Islam; Studi Kasus di Kelurahan Gladak Anyar Kecamatan Kota Kabupaten Pamekasan - M. Fahmi Afif; Yustafad (Universitas Islam Tribakti Lirboyo Kediri, 2022)
This research focuses on endogamous marriages of Arab descent in Pamekasan district, in general they still practice marriages like this, namely marriages in which the husband and wife come from the same tribe. In Indonesia, many endogamous marriages still occur on the basis of the similarity of customs, race, ethnicity and religion. Benchmarks for the existence of endogamous marriages can be chosen from the many studies that discuss endogamous marriages that occur in Indonesia. In practice, endogamous marriage does not occur directly, but there are processes that occur in the midst of society, such as selecting a mate, and continuing to the marriage level. This research is qualitative in nature and the data obtained through the interview method. From this research there are five fundamental factors. First, it's easier to adapt. Second, Protecting offspring. Third, the culture of the ancestors. Fourth, Kafa'ah. Fifth, the similarities between some Arab cultures and Madurese culture.